Numerical simulation of axially impacted elastic bar - Hamdani, Adib (IOP Publishing, 2022)
This numerical analysis considers a model of an elastic cylindrical bar impacted by rigid mass, where the accuracy of the model is benchmarked by a closed-form solution developed for this impact process. The analytical solution provides theoretical background and understanding, however, practical problem is not always restricted to a simple one-dimensional geometry and boundary conditions of a purely elastic material behaviour. Hence, the current work numerically simulates the impacted elastic bar, then explores parameters which are not considered in its theoretical model. A two-dimensional (2D) solid axisymmetric system is considered, in which rigid impactor is assigned with initial velocity corresponding to certain drop height and a 2D contact type is defined between interacting bodies. Both elastic and time-dependent viscoelastic material models are considered in this study. The simulation results reveal time intervals gradually increase in every sequential intervals, while relatively small discrepancies are recorded for peak load and pulse width outputs. The parameters of impactor's mass, drop height and structural stiffness are varied; showing how these parameters individually affect the resulting force response at end struck. The models then evaluate time-dependent viscoelastic material model; showing stiffer response of the resulting force in comparison to models assigned with long-term elastic moduli. Derived elastic modulus-output variable relations show comparable mathematical forms to corresponding equations formulated analytically.